Exploring Modern Architecture in Santa Maria (RS): The Case of the São Silvestre Building (1967) by Jayme Mazzucco - Peixoto, Luize Dal Rosso de Amaral; Souto, Ana Elisa Moraes (National Journal of City Management, 2025)
Objective:To analyze the presence and evolution of modern architecture in the state of Rio Grande do Sul, with a special focus on the city of Santa Maria. The study aims to demonstrate the importance of the São Silvestre Building (1967), designed by Jayme Mazzuco, within the context of modern architecture in the region and its integration with the city's urban center.Methodology: The research adopts a qualitative and historical approach, based on bibliographic review and architectural analysis. The study draws on references from international and local modern architecture, particularly the influence of the Carioca school, and examines Mazzuco’s work through a project-based reading within its local context.Originality/Relevance: This study addresses a theoretical gap by bringing visibility to modern architectural production outside major urban centers, highlighting the uniqueness of modern architecture in Santa Maria. Its academic relevance lies in recognizing the work of architect Jayme Mazzuco in regional contexts and understanding the local adaptations of modern architecture.Results: Findings indicate that the São Silvestre Building incorporates key elements of modern architecture in Rio Grande do Sul, such as brise-soleils (grilles), cobogós, and the use of regional materials. The building establishes a harmonious dialogue with other modern constructions in the city center. The research also reveals the significant professional and academic influence of Jayme Mazzuco on the development of modern architecture in Santa Maria.Theoretical/Methodological Contributions: The study deepens the theoretical understanding of modern architecture in Santa Maria and proposes a project-reading methodology suited to regional centers, encouraging more contextualized analyses of Brazilian modern architectural production.Social and Environmental Contributions: The article highlights the importance of preserving Santa Maria’s modern architectural heritage and recognizing the contributions of distinguished architects like Jayme Mazzuco. It promotes cultural appreciation and historical awareness of the urban landscape. Additionally, it emphasizes the architect's social role in shaping public policy and educating future generations through university teaching.
Keywords: Modern Architecture in Santa Maria; Jayme Mazzuco; São Silvestre Building